Efficient multiresidue determination method for 168 pharmaceuticals and metabolites: Optimization and application to raw wastewater, wastewater effluent, and surface water in Beijing, China. (June 2020) - Zhang, Yizhe; Duan, Lei; Wang, Bin; Liu, Cristina Su; Jia, Yanbo; Zhai, Nannan; Blaney, Lee; Yu, Gang
Abstract: New analytical methods are needed to efficiently measure the growing list of priority pharmaceuticals in environmental samples. In this regard, a rapid, sensitive, and robust method was developed for quantitation of 168 pharmaceuticals and pharmaceutical metabolites using solid-phase extraction (SPE) and liquid chromatography with tandem mass spectrometry. The extraction protocol and instrumental efficiency were specifically addressed to increase analytical workload and throughput. The optimized protocols, which are five times more efficient than US EPA Method 1694, enabled analyte recoveries that ranged from 77% to 117% for 162 analytes with method quantitation limits (MQLs) as low as 0.1 ng L −1 . To verify the suitability of the improved analytical method for environmental samples, 24-h composite samples of raw wastewater and wastewater effluent, along with downstream surface water, were analyzed. Overall, 143/168 target compounds were identified in at least one of the samples, and 130/168 analytes were present at concentrations above their MQLs. The total mass concentration of the measured analytes decreased by 93% during wastewater treatment. The analyte concentrations in the wastewater effluent were comparable to those measured in surface water 1 km downstream of the wastewater discharge point. Ultimately, the comprehensive method will serve as an important tool to inform the occurrence, fate, transport, and toxicity of a large suite of priority pharmaceuticals and pharmaceutical metabolites in natural and engineered systems. Graphical abstract: Image 1 Highlights: Cleanert PEP-2 SPE cartridges exhibited the best overall analyte recovery. 168 pharmaceuticals were measured by LC-MS 2 with 2 detection modes (27 min total). 92 analytes were quantified in surface water at a total concentration of 3.9 μg L −1 180 g/d of 30 antimicrobials were discharged into receiving water from the WWTP. Antihypertensives & antipsychotics were most recalcitrant in wastewater treatment.